Highly divergent sympatric lineages of Leptotila verreauxi (Aves: Columbidae) suggest a secondary contact area in the Isthmus of Tehuantepec, Mexico - Orlando J. Espinosa-Chávez; Adolfo G. Navarro-Sigüenza; Hernando Rodríguez-Correa; Luis A. Sánchez-González (Avian Research)
Due to a complex geological and biotic history, the Isthmus of Tehuantepec (IT), has been long recognized as a driver for the evolutionary divergence of numerous lowland and highland taxa. Widely distributed in the lowlands of the American continent, the White-Tipped Dove (Leptotila verreauxi) is a polytypic species with 13 recognized subspecies. Four of these have been recorded in Mexico, and the distribution of three abuts at the IT, suggesting a contact zone. To estimate phylogenetic patterns, divergence times and genetic differentiation, we examined two mtDNA (ND2 and COI) and one nDNA (β-fibint 7) markers. We also used correlative ecological niche models (ENM) to assess whether ecological differences across the IT may have acted as a biogeographical boundary. We estimated paleodistributions during the Middle Holocene, Last Glacial Maximum and Last Interglacial, to evaluate the influence of climate changes on the distribution and demographic changes. Our results showed genetically distinct lineages that diverged approximately 2.5 million years ago. Climatic and ecological factors may have played a dual role in promoting differentiation, but also in the formation of a secondary contact zone in the southern IT. Our ecological niche comparisons indicated that the ecological niche of sympatric lineages at the IT are not identical, suggesting niches divergence; in addition, environmental niche models across the region indicated no abrupt biogeographic barriers, but the presence of regions with low suitability. These results suggest that genetic differentiation originated by a vicariant event probably related to environmental factors, favored the evolution of different ecological niches. Also, the absence of a biogeographic barrier but the presence of less suitable areas in the contact regions, suggest that secondary contact zones may be also maintained by climatic factors for the eastern group, but also by biotic interactions for the western group.